Factors Affecting Customer Satisfaction: The Case of Ethiopia Hotel, Addis Ababa - Emebet Shibru Assefa (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2024)
The research topic in this study was to investigate the link between service quality, customer expectations, customer complaints, customer satisfaction, and customer loyalty in the Ethiopian hotel. The research method adopted for the study was explanatory, non-experimental quantitative research based on the convenient sampling technique that targeted 300 hotel customers in Ethiopia using both primary and secondary data collection tools. The findings revealed several key insights: Service quality with customer expectation was found to have a positive link with customer satisfaction while customer complaint also has a direct positive effect on customer satisfaction means complaints can provide a chance to improve customer satisfaction with the hotel. This research also reveals that there is no straight relationship between customer satisfaction and customer loyalty this might be so because other factors than satisfaction such as brand image, customer perceived value, and engagement may play a vital role in this regard. The scholars suggest hotel managers practice customer-oriented strategies for the identification of effective complaint handling, Customer Perceived Value increase, Company Reputation improvement, and the acknowledgment of the factors that contribute to Customer Loyalty. The practical implications include developing a targeted strategy to improve customer experience and retention.